2010
DOI: 10.1016/j.aap.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Externality of risk and crash severity at roundabouts

Abstract: The severity of 1491 crashes on 148 roundabouts in Flanders-Belgium was examined in order to investigate which factors might explain the severity of crashes or injuries and to relate these factors to the existing knowledge about contributing factors for injury severity in traffic.Logistic regression and hierarchical binomial logistic regression techniques were used.A clear externality of risk appeared to be present in the sense that vulnerable road user groups (pedestrians, bicyclists, moped riders and motorcy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 17 publications
0
27
1
Order By: Relevance
“…Another disadvantage of ÷ 2 is that it requires a sufficient sample size in order for the ÷ 2 approximation to be valid (NIST/Sematech, 2003). Three studies (Daniels et al, 2010;Malyshkina and Mannering, 2009;Srinivasan, 2002) were found to use ÷ 2 as the model goodness-of-fit test.…”
Section: Other Measuresmentioning
confidence: 99%
“…Another disadvantage of ÷ 2 is that it requires a sufficient sample size in order for the ÷ 2 approximation to be valid (NIST/Sematech, 2003). Three studies (Daniels et al, 2010;Malyshkina and Mannering, 2009;Srinivasan, 2002) were found to use ÷ 2 as the model goodness-of-fit test.…”
Section: Other Measuresmentioning
confidence: 99%
“…A first research stream focuses on specific aspects related to crash severity such as driver socio-economic characteristics (10), driver behavior (11), driver distraction (12), seatbelt use (e.g., 13,14), aggressive driving (15), vehicle and crash characteristics (16), vehicle age (17), weather conditions (e.g., 18), traffic congestion (19), regional economic conditions (20), roadside features (21), and highway design exemptions (22). A second research stream concentrates on the relation between crash severity and specific road section types such as intersections (e.g., 23,24), arterials and highways (e.g., 25,26,27) and roundabouts (28). A third research stream explores the link between crash severity and specific vehicle types such as large trucks and sport-utility vehicles (29,30,31), or specific crash types such as left-turn crashes (32).…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recent ordered-response model estimations account for heteroscedasticity (e.g., 30,34) and multiple joint models (e.g., 14,15,31,36). In order to relax two restrictive assumptions of traditional ordered-response models, namely inability to accommodate correlations across alternatives (21) and directionality constraints on the effect of the variable across outcomes (39), discrete categorical models have been estimated, such as multinomial logit (e.g., 11,16,33,35,39), nested logit (e.g., 21,25,28,40), and mixed logit (e.g., 22). In parallel, recent studies employ generalized ordered-response models (e.g., 19,32) that overcome the directionality constraints by relaxing the proportional odds assumption embedded in traditional ordered-response models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still at roundabouts road crashes occur because of various factors including the driver, vehicle, roadway and environment. There are several road safety researches conducted with the aim to: estimate the effects of roundabout geometric features [1][2][3][4][5], identify the potential locations for safety improvement [6][7][8][9][10][11], improve the vehicular operation [12][13][14], account the driver behaviour [15,16], and examine the before-and after scenarios [17][18][19]. Modifying geometric feature of the roundabouts has been found to reduce the number of crashes, in particular these treatments can be design to support a particular type of potential crashes.…”
Section: Introductionmentioning
confidence: 99%